Automating Sharepoint 2010 with Windows Powershell 2.0 - Lapointe, Gary (Serious skills., 2011)
"Authoritative coverage of the latest version of Microsoft's fastest-selling productImagine being able to perform a task that requires dozens of clicks with just a single command, or automate a series of identical tasks rather than repeat them. This book shows you how to do just that?and more?by using Windows PowerShell cmdlets with SharePoint 2010. Focused on everyday and frequently performed tasks, this invaluable guide provides PowerShell solutions for maintaining a SharePoint environment and explains how more than 500 cmdlets that come with SharePoint 2010 allows you to automate just about anything. Step-by-step instructions walk you through the necessary concepts and real-world examples enhance your learning process. Highlights the ways in which PowerShell cmdlets take the tedium out of executing frequently performed commands in SharePoint 2010 by automating everyday tasks Explains how to install and configure a SharePoint environment Details the steps for deploying and managing Web applications, site collections, authentication, and solution packages Shows you how to manage operational settings and back up and restore data Automating SharePoint 2010 with Windows PowerShell 2.0 helps you save time and effort performing common tasks so that you can be more productive"--